2015
DOI: 10.5603/fc.2015.0023
|View full text |Cite
|
Sign up to set email alerts
|

Udar mózgu jako pierwsza manifestacja migotania przedsionków — opis dwóch przypadków klinicznych

Abstract: Migotanie przedsionków (AF) jest najczęstszym zaburzeniem rytmu serca stwierdzanym u osób z udarem mózgu. Uważa się je za główne źródło zatorowości kardiogennej stwarzające istotne ryzyko powikłań zatorowo-zakrzepowych. W pracy opisano dwa przypadki kliniczne osób z nowo rozpoznanym AF, u których jego pierwszą manifestacją był udar niedokrwienny mózgu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In the Warsaw Stroke Register carried out in the years 1991 -1992, in the group of patients with stroke diagnosed for the first time, AF occurred in 26% of patients. Niewada et al In the hospital registry carried out in 2001-2002 showed that every third patient with ischemic stroke suffered from AF [9].…”
Section: Admissionmentioning
confidence: 99%
“…In the Warsaw Stroke Register carried out in the years 1991 -1992, in the group of patients with stroke diagnosed for the first time, AF occurred in 26% of patients. Niewada et al In the hospital registry carried out in 2001-2002 showed that every third patient with ischemic stroke suffered from AF [9].…”
Section: Admissionmentioning
confidence: 99%